2016
DOI: 10.2105/ajph.2016.303454
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Use and Cyclist Safety Following Boston’s Bicycle Infrastructure Expansion, 2009–2012

Abstract: The expansion of Boston's bicycle infrastructure was associated with increases in both bicycle use and cyclist safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…Indeed, nearly all bicyclists in our study used a helmet, wore reflective gear, had front and rear lights on their bicycles, and had their bicycles serviced within three months prior to the accident, suggesting the next steps in improving bicycle safety may need to center around city infrastructure and factors beyond the individual cyclist. For example, creating dedicated bicycle lanes has led to increasing bicycle use and decreased likelihood of being struck by a motorist [18]. Supporting this is the observation that over half of all survey respondents in our study predominantly rode their bicycles on roads without bike lanes and trended strongly towards sustaining significantly more severe injuries.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, nearly all bicyclists in our study used a helmet, wore reflective gear, had front and rear lights on their bicycles, and had their bicycles serviced within three months prior to the accident, suggesting the next steps in improving bicycle safety may need to center around city infrastructure and factors beyond the individual cyclist. For example, creating dedicated bicycle lanes has led to increasing bicycle use and decreased likelihood of being struck by a motorist [18]. Supporting this is the observation that over half of all survey respondents in our study predominantly rode their bicycles on roads without bike lanes and trended strongly towards sustaining significantly more severe injuries.…”
Section: Discussionsupporting
confidence: 60%
“…Currently, cycling represents 2% of all transportation modes; the City of Boston has set a goal to increase this number to 10% by 2020 through investments and initiatives to increase bicycle-friendly infrastructure [16,17]. Indeed, Boston bicycle commuting has increased by 82% between 2008 and 2011, accompanied by an increase in cyclist-friendly infrastructure [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the odds of sustaining and injury decreased by 14% over the 4 years (2009 to 2012) in which bicycle lane mileage was increased 5. In terms of surveillance, BPD planned to implement software that would capture more details about crashes.…”
Section: The City’s Responsementioning
confidence: 99%
“…The Boston Transportation Department (BTD) is the transportation planning and road engineering agency for the city. Launched in 2007, the city’s Boston Bikes programme expanded bicycle infrastructure, increasing the lane mileage from 0.34 to 92.2 by 2014 as well as designating bicycle parking spaces and partnering with Hubway, a bicycle share programme 5. At the city level, injury reports come from BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Several cities around the world have been promoting and encouraging the use of the bicycle for transportation purposes (Hirsch et al 2017, Johansson et al 2017. They have done so by investing in public infrastructure and implementing traffic laws and regulations that protect cyclists (Garrard et al 2008, Gorobets 2016, Pedroso et al 2016, Digioia et al 2017, Winters et al 2018. Some cities such as Copenhagen and Amsterdam are world leaders in the promotion and use of the bicycle, with as much as 40% of their population using the bicycle for commuting purposes on a daily basis.…”
mentioning
confidence: 99%